THE PLACE OF THE CHURCH IN THE SOCIO-POLITICAL AND ECONOMIC LIBERATION OF NIGERIA - Uchegbue, Christian Onyenaucheya (European Scientific Journal, ESJ, 2013)
This paper sought to point out the glaring and undeniable need for socio-political and economic liberation in Nigeria. It centred primarily on the prominent role religion, particularly the Christian religion, can play in achieving this noble project and pursuit of socio-political and economic liberation. By adopting the historical method of documentary analysis, these issues were discussed under three broad sections. The first section attempted a clarification of the key concept, ‘Church’ as used in the paper. The second section discussed the reality of the need for socio-political and economic liberation in Nigeria, tracing it from the global via the Third World situations. The third section dealt with the religious factor in achieving the desired socio-political and economic liberation in Nigeria. This was based on the radical potency and capacity of the Church for confronting and transforming the unjust social order. However, maintaining that the Church as a body should not get herself involved in partisan political activism, the paper outlined some possible functions by which the Church in Nigeria can contribute immensely towards the desired liberation. These included prophetic denunciation of the oppressive mechanism; promoting programmes of raising social consciousness among the masses; practical alleviation of the conditions of the oppressed masses; peace building through positive reconciliation of the oppressed and oppressive members; and personal conversion of the ordinary man. The paper concluded that a combination of the task of spiritual and social liberation enhances the Church, more than any other institution, to influence the socio-political and economic life of the Nigerian society so positively as to restore justice, equity and peace.